Human Leukocyte Antigen Distribution in German Caucasians with Advanced Ewing’s Sarcoma - Thiel, U.; Wolf, P.; Wawer, A.; Blaeschke, F.; Grunewald, T.G. P.; von Lüttichau, I. T.; Klingebiel, T.; Bader, P.; Borkhardt, A.; Laws, H.-J.; Handgretinger, R.; Lang, P.; Schlegel, P. G.; Eyrich, M.; Gruhn, B.; Ehninger, G.; Koscielniak, E.; Klein, C.; Sykora, K.-W.; Holler, E.; Mauz-Körholz, C.; Woessmann, W.; Richter, G.H. S.; Schmidt, A. H.; Peters, C.; Dirksen, U.; Jürgens, H.; Bregni, M.; Burdach, S. (Klinische Pädiatrie, 2012)
Risk stratification criteria for patients with Ewing’s sarcoma family of tumors (ESFT) are still limited. We hypothesized divergent human leukocyte antigen (HLA) patterns in ESFT patients and compared HLA-A, -B and -DR phenotype frequencies of patients with advanced ESFT with those of healthy controls.HLA types of all German Caucasian patients with advanced ESFT and available HLA-A, -B and -DR data registered in the European Group for Blood and Marrow Transplantation, Paediatric Registry for Stem Cell Transplantation and the MetaEICESS data bases (study group, n=30) were retrospectively compared with HLA types of healthy German stem cell donors (control group, n=8 862 for single HLA frequencies and n=8 839 for allele combinations). Study group patients had been immuno-typed due to eligibility for allogeneic stem cell transplantation for high risk of treatment failure, and thus constituted a selected subgroup of ESFT patients.After Bonferroni correction for multiple testing (PC), phenotype frequencies of HLA-A24 remained significantly higher in the study group compared to controls (PC<0.05). Furthermore, several HLA combinations were significantly more frequent in the study group compared to controls (all PC<0.05).We report an increased incidence of circumscribed HLA patterns in German Caucasians with advanced ESFT. The possible clinical significance of this observation has to be re-assessed in prospective trials comprising larger ESFT patient numbers of all risk groups.
Keywords: Ewing’s sarcoma; human leukocyte antigens; risk stratification; biomarkers; immunosurveillance; allogeneic stem cell transplantation